If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -10 = 4xm + 14 Reorder the terms: -10 + -8x = 4xm + 14 Reorder the terms: -10 + -8x = 14 + 4mx Solving -10 + -8x = 14 + 4mx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4mx' to each side of the equation. -10 + -4mx + -8x = 14 + 4mx + -4mx Combine like terms: 4mx + -4mx = 0 -10 + -4mx + -8x = 14 + 0 -10 + -4mx + -8x = 14 Add '10' to each side of the equation. -10 + -4mx + 10 + -8x = 14 + 10 Reorder the terms: -10 + 10 + -4mx + -8x = 14 + 10 Combine like terms: -10 + 10 = 0 0 + -4mx + -8x = 14 + 10 -4mx + -8x = 14 + 10 Combine like terms: 14 + 10 = 24 -4mx + -8x = 24 Reorder the terms: -24 + -4mx + -8x = 24 + -24 Combine like terms: 24 + -24 = 0 -24 + -4mx + -8x = 0 Factor out the Greatest Common Factor (GCF), '-4'. -4(6 + mx + 2x) = 0 Ignore the factor -4.Subproblem 1
Set the factor '(6 + mx + 2x)' equal to zero and attempt to solve: Simplifying 6 + mx + 2x = 0 Solving 6 + mx + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + mx + -6 + 2x = 0 + -6 Reorder the terms: 6 + -6 + mx + 2x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + mx + 2x = 0 + -6 mx + 2x = 0 + -6 Combine like terms: 0 + -6 = -6 mx + 2x = -6 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 2*4+4y=13 | | 5x+x(1.05)=2159833 | | 10b^2-68b-14=0 | | -11j-6+3j=-30 | | -4-5x-6x=-26 | | -4-5x-6x=-2 | | 9x^2-36x+29=-3 | | 28=8b+13b-35 | | -4+3x+7x=-94 | | -9(2x+4)+18x=45 | | 7+8x=-57 | | 0.05x-0.01y=0.7 | | 7+6x+2x=-57 | | -43=12-6p+p | | 15x-1/3=-1/3 | | 8b^2+57b-56=0 | | y=-9/4*.67-9 | | -9+6x+2x=-1 | | 1/8a-6=-2 | | y=-9/4*.67 | | 3k+2k=60 | | 2+-5+4= | | y=-9/4*.6780-9 | | 6x-10=3x-4 | | 5x-2=3+4x+5 | | a-0.5=1.5 | | y=7/10*.6780-7 | | y=7/10*.67-7 | | 26-2z=3(2-4z) | | 134.00=.75x+29 | | (x+9)(x-1)=(x+3) | | 8=t/-3+4 |